Improvisation, computers and the unconscious mind. - Teitelbaum, Richard (Contemporary Music Review, 2006)
The author describes some of his musical improvisations. He also discusses the basic concept of the mental processes involved in the kind of free improvisation he practiced for several years, and the enhancements that the development of electronic technology has facilitated. The author focuses on the relationship between the origins of material generated in the improviser's unconscious and its musical realization in performance.